Table of Content - - (Journal of Islamic Sciences, 2023)
Table of Content 1. Examples of jurisprudential rules and their applications in the judgments of social media Mrs. Nadira Tariq Al-Omar 2. The Modern Interpretation of the Prophet’s Sunnah (Purposes and Risks) Dr. Hamzah Faiei Ibraheem Alfathi 3. Christian-Islamic dialogue and Orientalism problem Mrs. Nora Mohammed Al-Ajmi 4. The sent interests at Al-Hanafiyya and their contemporary applications in personal status Mr. Rakan Khalaf Mahasneh Almwadih 5. Timeline for An-Nisa’ based on occasions of revelation Mr. Rashid Issack Ali 6. Treasure is a creature, not a creator Prof. Ibtissam Ibrahim Baydoun 7. Substantive defenses in the cases of the donor in the donation lawsuits Mrs. Razan Yousef Al-Wazzan, Co-Prof. Asim Abdullah Al-Mutawa